The democraticness of traditional political systems in Africa. Issue 2 (17th February 2022) - Neupert-Wentz, Clara; Kromrey, Daniela; Bayer, Axel
ABSTRACT: Traditional political systems (TPS) are an important part of the political landscape in Africa. They govern subnational communities and differ from nation states, both in their institutional set-up as well as in their legitimacy. Yet, we have little comparative knowledge on these political systems and, in particular, whether they can be described as democratic. In this article, we analyse the democraticness of TPS based on a new expert survey. Using confirmatory factor analysis (CFA), we show that the more than 140 ethnic groups we analyse vary meaningfully in their democraticness. Measures of public preference input and of political process control contribute particularly to a latent measure of democraticness. Furthermore, we find some indication for regionally interdependent institutions, with slightly more democratic systems in Southern Africa and less democratic systems in West Africa. Yet, no such interdependence exists between the state and the group level. Finally, we find that more hierarchically organized political systems, kings, and chiefs, as well as those organized in segments, are on average less democratic, while the presence of elders is associated with higher levels of democraticness.